Methods of Expressing Parcellation Phenomenon in Karakalpak Language - Dosjanova, Gulnaz; Kazakhbaeva, Anargul; Erjanova, Dilfuza (International Journal of Membrane Science and Technology, 2023)
In this article, the characteristic features of the parcellation phenomenon in the Karakalpak language are analyzed on the example of the works of T. Kaipbergenov. The skill of the writer in revealing the characteristics of the hero through the parcellation phenomenon is shown. Also, information on the methods of expressing of this phenomenon in oral speech, literary text, its place is given. The difference of parcellation units from other linguistic phenomena is determined.The study of the phenomenon of parcellation in general linguistics, linguistic units equaled to this phenomenon, and their differences are shown.